2017
DOI: 10.13005/bbra/2557
|View full text |Cite
|
Sign up to set email alerts
|

Combined Application of Different Species of Trichoderma and Pseudomonas fluorescens on the Cellulolytic Enzymes of Fusarium Oxysporum for the Control of Fusarium wiltDisease in Arachis hypogea. L

Abstract: Fusarium oxysporum causes Fusarium wilt of crop plants leads to considerable yield loss. The study was conducted to determine the beneficial effects of combining Trichoderma species and Pseudomonas fluorescens i.e Trichodema viride+ Pseudomonas fluorescens (Tv+Pf) (1+2%), Trichoderma harzianum+Pseudomonas fluorescens (Th+Pf) (1.5+2%), Trichoderma viride +Trichoderma harzianum (Tv+Th) (1+1.5%) on the activity of cellulolytic enzymes of Fusarium oxysporum to control Fusarium wilt of Arachis hypogaea. L wilt in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The endoglucanases and proteases produced by Pantoea, Mitsuaria, and Enterobacter, studied here, were reported previously (Das et al, 2017;Fan et al, 2016). These enzymes degrade the fungi cell wall, decreasing their populations in the soil and damaging effects on the plant (Jayasekara & Ratnayake, 2019;Rajeswari & Kapoor, 2017).…”
Section: Discussionmentioning
confidence: 59%
“…The endoglucanases and proteases produced by Pantoea, Mitsuaria, and Enterobacter, studied here, were reported previously (Das et al, 2017;Fan et al, 2016). These enzymes degrade the fungi cell wall, decreasing their populations in the soil and damaging effects on the plant (Jayasekara & Ratnayake, 2019;Rajeswari & Kapoor, 2017).…”
Section: Discussionmentioning
confidence: 59%
“…Between 55 and 85% of peanut root rot ( Chen et al, 2022 ) is caused by a series of pathogenic microorganisms, including Aspergillus niger ( Sharma et al, 2012 ), A. flavus ( Zhao et al, 2019 ), Sclerotinia spp. ( Rajeswari and Kapoor, 2017 ), and Fusarium spp. ( Sun et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Talaviya and Jadega (2015) reported that combined application of T. viride+ T. harzianum+ Pseudomonas fluorescens was significantly effective in controlling cumin wilt disease and improves higher yield. Rajeswari and Kapoor (2017) DNA estimation: In DNA estimation, the method of Burton (1956) was used. To 1.5 ml of PCA extract, 3ml of diphenylamine reagent was added.…”
Section: Introductionmentioning
confidence: 99%